1993
DOI: 10.1212/wnl.43.12.2674
|View full text |Cite
|
Sign up to set email alerts
|

Somatic instability of CTG repeat in myotonic dystrophy

Abstract: An unstable expansion of the CTG repeat in the 3' untranslated region of the myotonin protein kinase (MT-PK) gene is the mutation specific for myotonic dystrophy (DM). To examine somatic stability of the repeat, we studied tissue variability of the repeat size. In five DM patients, the restriction fragment containing the repeat region was substantially larger in skeletal muscle than in peripheral blood leukocytes (PBL). In addition, one normal subject showed a size discrepancy in one of the normal alleles by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
3

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 0 publications
5
96
0
3
Order By: Relevance
“…The characteristics of DM dynamic mutation have been reported in English (Harley et al, 1992b(Harley et al, , 1993, French (Lavedan et al, 1993), Spanish (Cobo et al, 1993), Canadian (Hunter et al, 1992Tsilfidis et aL, 1992;Barcelo et al, 1993). Australian (Mulley el al., 1993), and American people (Ashizawa et aL, , 1993(Ashizawa et aL, , 1994aRedman et al, 1993). We previously showed that CTG expansion was also detected in Japanese DM .…”
Section: Introductionmentioning
confidence: 89%
“…The characteristics of DM dynamic mutation have been reported in English (Harley et al, 1992b(Harley et al, , 1993, French (Lavedan et al, 1993), Spanish (Cobo et al, 1993), Canadian (Hunter et al, 1992Tsilfidis et aL, 1992;Barcelo et al, 1993). Australian (Mulley el al., 1993), and American people (Ashizawa et aL, , 1993(Ashizawa et aL, , 1994aRedman et al, 1993). We previously showed that CTG expansion was also detected in Japanese DM .…”
Section: Introductionmentioning
confidence: 89%
“…Whilst in the main such observations usually correlate quite well with the observed clinical anticipation, quite a high proportion of cases have been demonstrated apparent reductions in the allele length not associated with an improvement of the patients clinical symptoms. 10 Since it is known that the expanded CTG repeat is highly unstable in both somatic tissues 11,12 and in the male germline, 13,14 some account of these factors needs to be made in interpreting measured intergenerational differences, given that the somatic changes in repeat length could influence the interpretation of intergenerational changes. Detailed studies of somatic mosaicism have revealed that it is tissue specific, [11][12][13] biased toward further expansion and continuous throughout the life of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…10 Since it is known that the expanded CTG repeat is highly unstable in both somatic tissues 11,12 and in the male germline, 13,14 some account of these factors needs to be made in interpreting measured intergenerational differences, given that the somatic changes in repeat length could influence the interpretation of intergenerational changes. Detailed studies of somatic mosaicism have revealed that it is tissue specific, [11][12][13] biased toward further expansion and continuous throughout the life of an individual. [14][15][16][17] Clearly, progressive somatic mosaicism has implications for interpreting intergenerational transmissions based on the analysis of average allele sizes in the blood of parent and offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The size of expansion correlates to a reasonable degree with the clinical symptoms not only within a given family but also within each internal organ of one body (9)(10)(11)(12)(13). Disturbed glucose tolerance is a well-knowncomplication of the disease showing elevated plasma insulin levels and a normal response to exogenous insulin (2,4).…”
Section: Discussionmentioning
confidence: 99%